2008
DOI: 10.1063/1.2963027
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of backward spin waves in a one-dimensional magnonic crystal

Abstract: Scattering of backward volume magnetostatic spin waves from a one-dimensional magnonic crystal, realized by a grating of shallow grooves etched into the surface of an yttrium-iron garnet film, was experimentally studied. Rejection frequency bands were clearly observed. The rejection efficiency and the frequency width of the rejection bands increase with increasing groove depth. A theoretical model based on the analogy of a spin-wave film-waveguide with a microwave transmission line was used to interpret the ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
203
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(212 citation statements)
references
References 17 publications
5
203
0
4
Order By: Relevance
“…The spin-wave dispersion relation depends on many parameters, such as the geometry of the spin-wave waveguide (film thickness and waveguide width), external magnetic field H ext , and saturation magnetization M S . In fact, all of these parameters have already been used to fabricate magnonic crystals [6][7][8]12,13,[18][19][20] : arrays of metallic stripes, etched grooves or antidots, biasing magnetic field or periodic variation of the saturation magnetization using ion implantation.However, all available methods for the fabrication of such spintronic devices result in spatially constant magnetic materials. J. Topp et al have shown that the parameters of magnetic materials can be changed locally after the rather time-consuming fabrication of the spintronic device 21 -but the functionality of the device stays the same.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The spin-wave dispersion relation depends on many parameters, such as the geometry of the spin-wave waveguide (film thickness and waveguide width), external magnetic field H ext , and saturation magnetization M S . In fact, all of these parameters have already been used to fabricate magnonic crystals [6][7][8]12,13,[18][19][20] : arrays of metallic stripes, etched grooves or antidots, biasing magnetic field or periodic variation of the saturation magnetization using ion implantation.However, all available methods for the fabrication of such spintronic devices result in spatially constant magnetic materials. J. Topp et al have shown that the parameters of magnetic materials can be changed locally after the rather time-consuming fabrication of the spintronic device 21 -but the functionality of the device stays the same.…”
mentioning
confidence: 99%
“…Transfer matrices are used to describe the propagation of electromagnetic signals through media. They may thus be applied to model, for example, the propagation of spin waves in a magnonic crystal designed with sharp grooves etched into the YIG layer 12 . Here, for comparison of the experimental data against the theory, a transfer matrix approach is generalized for smooth one-dimensional thermal landscapes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such systems-which include optical photonic crystals [1][2][3][4][5][6][7] and magnetic magnonic crystals [8][9][10][11][12][13][14][15]-belong to the class of so-called metamaterials: synthetic media with properties derived from an engineered mesoscopic structure. The wave transmission spectra of artificial crystals typically include band gaps which arise as a result of resonant wave-lattice interactions analogous to the atomic-scale Bragg scattering phenomena observed in natural crystals [16].…”
mentioning
confidence: 99%